A comparison of coral reef survey methods line transect and quadrat. - Hismana, Raymond Romeo P.
Line Transect and Quadrat Methods were compared in the survey of Talisay reef flat in Taklong Island, Guimaras. Three 1x20 mFD plots were sampled noting parameters on growth forms, genera, hard coral cover, soft coral cover, algal cover, other fauna, abiotic cover and time of sampling, in order to provide an objective standard or control against which to test the results obtained by the different survey methods. Friedman's test on ranks shows that 10 quadrats for Quadrat Method and 2 lines for Line Transect Method can give the closest approximation of the control. Using 10 Quadrat Method and 2 Lines for Line Transect Method, both scorings of the two methods were compared with the control and with one another for significant differences. The researcher used the paired t-test on all the parameters except on growth forms, genera, and time which were descriptively analyzed using relations., The Quadrat Method recordwed more genera, estimated hard coral, soft coral, algal and abiotic cover accurately at 0.05 level of significance ( P > 0.05 ) and detected more rare features (other fauna). Line Transect Method in turn is more time efficient and has also recorded effectively soft coral and algal cover estimates at 0.05 level of significance ( P > 0.05 ).